Hidrogéis injetáveis a base de quitosana/gelatina/nanopartículas de vidro bioativo com potencial para regeneração óssea: estudo in vitro e in vivo - Cheisy Daiana Freitas Moreira (2018)
Hydrogels are hydrophilic polymeric network capable of retaining a large amount of water in their structure, without dissolving. Currently, biomedical researches are focused on the development of injectable hydrogels, which undergo gelation in situ by a thermal stimulus. In this study, new composite hydrogels based on the biopolymers chitosan and gelatin associated with bioactive glass nanoparticles were prepared. These nanocomposites were extensively characterized from a structural point of view, chemical composition and in vitro and in vivo behavior. Infrared Spectroscopy (FTIR) and zeta potential analyzes have allowed to elucidate some events related to the gelation process of the hydrogels, which occur through electrostatic interactions influenced by the temperature change. The zeta potential at 37 ºC ranged from +3.1 ± 1.4mV to +6.9 ± 3.2mV and showed the cationic nature of these hydrogels, which are capable of interacting with negatively charged molecules from native extracellular matrix (ECM). Rheological, seringability and injectability tests confirmed the administration viability of hydrogels via syringe and needle. The rheological test results showed that the addition of bioactive glass and gelatin increased the elastic properties of the hydrogels, presenting elastic modulus (G´) increasing from 5.4Pa for pure chitosan hydrogels to 12.4Pa for hydrogel composites with higher contents of gelatin and bioactive glass. Moreover, these systems showed a reduction in gelation time, which is desirable for clinical applications and may avoid the lixiviation of the hydrogels when implanted in ECM. In vitro and in vivo cytotoxicity assays confirmed the biocompatible nature of the formulations. In addition, the hydrogels were injected into tibial defects and showed better results in the formation of new tissue when compared to bone regeneration without the biomaterial. Hydrogels exhibited the physicochemical and biological characteristics that make then promising candidates for use as temporary injectable matrices for bone regeneration.